2018
DOI: 10.14254/2071-8330.2018/11-3/13
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in perception of the university education quality as applied to entrepreneurial intention

Abstract: The aim of this paper is to examine how university students perceive the selected attributes of university education quality in the context of their possible entrepreneurial activities and to explore the differences between genders in this regard. A total of 977 students from Czech and Slovak universities were surveyed. The Z-test for two population proportions was employed to test the hypotheses. The majority of university students positively perceived the quality of university education in general as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 73 publications
1
17
0
5
Order By: Relevance
“…Firms operating in Slovakia are more social responsible than those in the Czech Republic. This finding is in line with prior studies which identified some differences between the two countries in terms of business environment Khan et al, 2019;Koisova et al, 2018), or having substantial interest in entrepreneurship (Çera et al, 2018;Dvorský et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Firms operating in Slovakia are more social responsible than those in the Czech Republic. This finding is in line with prior studies which identified some differences between the two countries in terms of business environment Khan et al, 2019;Koisova et al, 2018), or having substantial interest in entrepreneurship (Çera et al, 2018;Dvorský et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Access to fi nancial resources is one of the main issues for entrepreneurs (Dacin et al, 2010; beside the insignifi cant economic results (Kashitsina et al, 2016). The issues related to access to fi nancial resources concern the banking sector support to companies, the existence of alternative fi nancial resources, state support in starting and developing a business (Gavurova et al, 2017).…”
Section: Yuriy Bilan Mihaela Simionescu Grzegorz Mentel Zoltan Rozsamentioning
confidence: 99%
“…The issues related to credit conditions of commercial banks discourage Czech students to start a business, issues related to credit conditions being previously mentioned by Dacin et al (2010). The state business support through different tools is not appreciated by students, the state system of support being criticized before by Oehler et al (2015).…”
Section: Business Administration and Managementmentioning
confidence: 99%
“…Likewise, Higher Education Institutions (HEI) have a determining role in generating and promoting entrepreneurship in societies, as long as they take into account the elements of entrepreneurship within the training of their students (Bartoš, Rahman, Horák, & Jáčová, 2015;Bazan et al, 2019;Çera, Cepel, Zakutna, & Rozsa, 2018;Cera, Mlouk, Cera, & Shumeli, 2020;Dvorský, Petráková, Zapletalíková & Rózsa, 2019;2018;Sołtysiak, 2014). In this sense, social entrepreneurship, promoted from the university level, can influence a new development model for societies, without focusing only on the economic benefit of professionals or institutions (British Council, 2016, Escámez, Peris & Escámez, 2017.…”
Section: Introductionmentioning
confidence: 99%